1988
DOI: 10.1002/mrc.1260260208
|View full text |Cite
|
Sign up to set email alerts
|

Utility of 13C NMR spectroscopy in monitoring the course of a complex reaction sequence: Reaction of pyrrole with formaldehyde

Abstract: The complex course of the reaction of pyrrole with formaldehyde has been completely elucidated by quantitative I3C NMR spectroscopy using the inverse-gated decoupling technique. The final product is 23-bis(hydroxymethy1)pyrrole (with a free l-position), but three main intermediates containing 1-hydroxymethyl groups were identified, and the rise and subsequent fall of their populations followed. The intermediacy of additional compounds (formals) also renders the reaction more complex. The molar fractions of fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Two adjacent CH 2 OH moieties can potentially form a ring via dehydration as illustrated by 5 to 7 in Figure . This reaction however is endergonic 6.6 kcal/mol with a calculated barrier of 21.3 kcal/mol, so we think species such as 7 are unlikely to remain stable in solution, and no mention of them is made in the NMR study …”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Two adjacent CH 2 OH moieties can potentially form a ring via dehydration as illustrated by 5 to 7 in Figure . This reaction however is endergonic 6.6 kcal/mol with a calculated barrier of 21.3 kcal/mol, so we think species such as 7 are unlikely to remain stable in solution, and no mention of them is made in the NMR study …”
Section: Resultsmentioning
confidence: 98%
“…Katritzky and Law conducted a low-temperature 13 C NMR study for the reaction of pyrrole with formaldehyde and found that 1 is indeed the first species formed . Small amounts of 9 are observed after 10 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation